41 Low Flow Priapism as A Complication of Covid-19 Infection. (12th October 2021) - Ahmed, S; Alabai, M; Datta, S
Abstract: On 12 March 2020 the World Health Organisation (WHO) declared a pandemic of SARS-COV-2(Covid 19). We report a case of a 58-year-old man who presented with dyspnoea, pyrexia and a dry cough. Upon admission he was noted to be in a severe Type 1 Respiratory Failure with Bi-lateral pulmonary infiltrates suggestive of Covid 19 infection. Rapid transfer to ITU ensued with Intubation, Ventilation and Inotropic support. Priapism was noted a day into admission which was subsequently aspirated by the Urology team, achieving detumescence. Priapism is a state of persistent penile erection that continues for 4 hours beyond sexual stimulation. We describe the role of thrombosis, dysregulation of the clotting cascade and acute disseminated intravascular coagulation (DIC) as shared pathologies in priapism and Covid 19 infection. We highlight the importance of vigilance for extra-pulmonary manifestations of Covid-19 and feel that the pro-thrombotic phenomena exhibited by Covid-19 infection affects distal vasculature in the same manner as Low Flow Priapism and hence explains why our patient suffered from this particular urological complication